The Dictatorship of Silence. The Victims of the Civil War and Franquism in Secondary School Books - Escobedo Muguerza, Isabel (Historia y Memoria de la Educación, 2022)
From its beginnings, the Franco dictatorship developed a policy of memory that tried, by all means, to demonise and then make the memory of the Second Republic disappear, burying with it all the victims of the Civil War and, of course, the victims of the dictatorship itself. Although it may seem surprising, more than forty years later, parts of this discourse transmitted about the Second Republic, the Civil War and Franco’s repression are still present not only among those generations who were educated in Franco’s institutions and their children, but also in school textbooks currently used in secondary schools. This fact reveals that, despite the fact that in recent decades a great deal of specialised research has been carried out on this period, the ideas and conclusions drawn from this research have not permeated school textbooks. This constitutes a major impediment to the transmission of this knowledge to the rest of society. In this sense, through the analysis of a good number of textbooks from different publishers, this study aims to analyse the proportion of textbook material devoted to this historical period in relation to the rest of the contents; the aspects covered most thoroughly in the textbooks - as opposed to those that are silenced or hidden - and, finally, the vision that is presented in these textbooks about the victims of the Civil War and Franco’s regime.